O sentido do trabalho para a pessoa com deficiência física por lesão medular - Guedes, Maria Helena Delanesi (2010)
This study aims to investigate the sense of the work for disabled people by cord injury. Usually, the injury occurs abruptly, interrupting the evolution and on going life projects and, although imposes physical limitations, does not affect directly the cognitive functions, what could facilitate the resume of professional life. The quest is based in Social-Historical Psychology that allows to develop aspects about: deficiency, rehabilitation, cord injury, work, social inclusion/exclusion, training integration/inclusion, function and meaning of work for people with disabilities. The dialogue between a person and the society interferes in the production of the sense of work, as well as in the construction of its subjectivity, expressing itself in the relation with the environment and, therefore, in the process of professional insertion/inclusion. The rehabilitation process aims to empower the person, physically and psychically to (re)assume his/her place in the society, developing his/her social roles, highlighting the importance of the sense of work for the person who faces disability. The quest follows a qualitative approach with semi-structured interviews with three (3) patients from the Instituto de Medicina Física e Reabilitação do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo IMREA HCFMUSP. The apprehension of the constitution of the senses is done through the speech analysis, through the Meaning Cores ( Núcleos de Significação ) developed by Aguiar e Ozella (2006), aiming the comprehension of the phenomena in the interface with the professional insertion. Similarities and differences resulting from the experienced dialogue are highlighted, creating a unique and singular human being, however, with common aspects in his/her essence. The work is seen as a way to achieve the independence and autonomy with the major objective of selfassertiveness. The sense of the work is not isolated, but is part of the social reality that is presented without, nevertheless, loose its singularity